1994
DOI: 10.1159/000117002
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Associated with Methamphetamine Inhalation

Abstract: Seven patients (all men, mean age 32 years, range 17-47) with stroke following methamphetamine inhalation were collected during the last 2 years. Like oral or intravenous abusers, our patients had more hemorrhagic (n = 5) than ischemic strokes (n = 2). Cases of intracerebral hemorrhage (ICH) were lobar (n = 3), caudate (n = 1) or putaminal (n = 1), whereas the infarctions were both in the middle cerebral artery region. Each stroke event occurred within 3 days after drug use. Three patients had hypertension on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 11 publications
2
40
1
1
Order By: Relevance
“…The present data further support the clinical observations that patients with a chronic or acute MA abuse history can develop cerebral hemorrhages in striatum and infarction in MCA distribution. 1,2 In conclusion, our data suggest that the use of MA exacerbates stroke-induced damage in the brain and that GDNF maybe involved in this response.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The present data further support the clinical observations that patients with a chronic or acute MA abuse history can develop cerebral hemorrhages in striatum and infarction in MCA distribution. 1,2 In conclusion, our data suggest that the use of MA exacerbates stroke-induced damage in the brain and that GDNF maybe involved in this response.…”
Section: Discussionmentioning
confidence: 59%
“…everal clinical studies have indicated that patients with a chronic or acute methamphetamine (MA) abuse history develop cerebral hemorrhages in striatum and infarction in the middle cerebral arterial (MCA) distribution area, 1,2 which suggests that the use of MA may be associated with brain ischemia. However, it is still not known whether administration of MA predisposes to ischemic brain insults and, if so, the potential mechanisms by which this occurs.…”
mentioning
confidence: 99%
“…Specifically, d-methamphetamine-induced hypertension and tachycardia have been associated with deaths or debilitating injury from ruptured berry aneurysms (Davis and Swalwell 1996), intracerebral hemorrhage (Selmi et al 1995;Shibata et al 1988;Yen et al 1994), and aortic dissection (Davis and Swalwell 1994). Indeed, d-methamphetamine's hypertensive effects, and the associated complications, may render it more toxic than cocaine because of its longer half-life (Davis and Swalwell 1996).…”
mentioning
confidence: 99%
“…ICH in young amphetamine addicts is usually a consequence of intravenous injection of the drug, 2,3) although ICH caused by oral ingestion or inhalation of amphetamines has been reported. 9) In summary, the urinalysis screening test for psychotropic agents including amphetamines should be included in the emergency room diagnostic process for young, non-hypertensive patients with ICH but no angiographical abnormalities.…”
Section: Discussionmentioning
confidence: 99%